Experiencing shame: An affective reading of the sexual and reproductive health and rights classroom in Bangladesh - Khan, Saad Adnan; Alam, Farhana; Rommesc, Els; Rashid, Sabina Faiz (Taylor & Francis, 2022)
This article was published in Annals of the New York Academy of Sciences [ © 2020 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/14681811.2019.1707651 The Journal's website is at: https://www.tandfonline.com/doi/abs/10.1080/14681811.2019.1707651?journalCode=csed20